Tsunami hazard in Lombok and Bali, Indonesia, due to the Flores back-arc thrust - R. P. Felix; J. A. Hubbard; J. A. Hubbard; K. E. Bradley; K. E. Bradley; K. H. Lythgoe; L. Li; L. Li; A. D. Switzer; A. D. Switzer (Natural Hazards and Earth System Sciences, 2022)
The tsunami hazard posed by the Flores back-arc thrust, which runs along the northern coast of the islands of Bali and Lombok, Indonesia, is poorly studied compared to the Sunda Megathrust, situated ∼250 km to the south of the islands. However, the 2018 Lombok earthquake sequence demonstrated the seismic potential of the western Flores Thrust when a fault ramp beneath the island of Lombok ruptured in two Mw 6.9 earthquakes. Although the uplift in these events mostly occurred below land, the sequence still generated local tsunamis along the northern coast of Lombok. Historical records show that the Flores fault system in the Lombok and Bali region has generated at least six ≥Ms 6.5 tsunamigenic earthquakes since 1800 CE. Hence, it is important to assess the possible tsunami hazard represented by this fault system. Here, we focus on the submarine fault segment located between the islands of Lombok and Bali (below the Lombok Strait). We assess modeled tsunami patterns generated by fault slip in six earthquake scenarios (slip of 1–5 m, representing Mw 7.2–7.9+) using deterministic modeling, with a focus on impacts on the capital cities of Mataram, Lombok, and Denpasar, Bali, which lie on the coasts facing the strait. We use a geologically constrained earthquake model informed by the Lombok earthquake sequence, together with a high-resolution bathymetry dataset developed by combining direct measurements from the General Bathymetric Chart of the Oceans (GEBCO) with sounding measurements from the official nautical charts for Indonesia. Our results show that fault rupture in this region could trigger a tsunami reaching Mataram in <9 min and Denpasar in ∼ 23–27 min, with multiple waves. For an earthquake with 3–5 m of coseismic slip, Mataram and Denpasar experience maximum wave heights of ∼ 1.6–2.7 and ∼ 0.6–1.4 m, respectively. Furthermore, our earthquake models indicate that both cities would experience coseismic subsidence of 20–40 cm, exacerbating their exposure to both the tsunami and other coastal hazards. Overall, Mataram is more exposed than Denpasar to high tsunami waves arriving quickly from the fault source. To understand how a tsunami would affect Mataram, we model the associated inundation using the 5 m slip model and show that Mataram is inundated ∼ 55–140 m inland along the northern coast and ∼230 m along the southern coast, with maximum flow depths of ∼ 2–3 m. Our study highlights that the early tsunami arrival in Mataram, Lombok, gives little time for residents to evacuate. Raising their awareness about the potential for locally generated tsunamis and the need for evacuation plans is important to help them respond immediately after experiencing strong ground shaking.